FAO economic and social development paper N.134: Rural informal credit markets and the effectiveness of policy reform - Alexander Sarris (FAO, 1996)
The study reviews three different strands of literature relevant to the topic. The largely macroeconomic literature on financial libralisation and growth has produced arguments favouring largely unregulated financial markets. This review has been challenged by structuralists who have emphasised the dually between formal and informal financial markets, and have argued that financial liberation policies are stagflationary. The second strand has a microeconomic focus, emphasises the imperfect information aspects of rural financial markets, and has sought to explain several observed phenomena in rural areas that apparently prevent the proper operation of formal financial intermediaries. This literature has emphasised the fact that rural loan transactions appear to have implications for many other rural markets, suach as the labour and product markets. Finaaly the literature on household consumption smoothing and food security strategies has sought to explain how households respond to considerable market and non-market risks in rural areas.